Recent advances in metal/ceria catalysts for air pollution control: mechanism insight and application. Issue 10 (14th September 2021) - Li, Qingzhu; Yan, Xuelei; Shi, Miao; Wang, Qingwei; Liu, Hui; Lin, Zhang; Huang, Xiaowei
Abstract : This work discussed the structure–activity relationship of metal/CeO2 catalysts, emphasized the theoretical calculation for catalytic mechanism insight and guiding the design of high-efficiency metal/CeO2 catalysts for air pollution control. Abstract : Metal element doping or loading on cerium dioxide (ceria, CeO2 ) to form metal/CeO2 heterogeneous catalysts, in which CeO2 acts as the active component, support and promoter, has proven to be an excellent catalytic system with a wide range of applications. Over the past few decades, many metal/CeO2 catalysts composed of different metals and CeO2 have been prepared for air pollution control. Moreover, the structure–activity relationship and catalytic mechanism of metal/CeO2 were scrutinized through theoretical calculation based on density functional theory (DFT) and various advanced physicochemical analysis methods. Thus, a timely review of the recent advances is necessary to inspire further research. The main aim of this review is to summarize the recent research progress of metal/CeO2 catalysts in the field of air pollution control, especially the removal of volatile organic compounds (VOCs), particulate matter (soot), NO x, elemental mercury (Hg 0 ), and hydrocarbons. The important role of interfacial interactions and oxygen vacancies (OVs) in the catalytic process is emphasized. In addition, the mechanism of the metal/CeO2 catalytic system is concisely presented based on the simulated properties of theoretical calculations as well as scientific design guidance for scenario-specific applications of metal/CeO2 catalysts. Finally, perspectives based on the research status of metal/CeO2 catalysts are proposed to provide reference and inspiration for the application of metal/CeO2 catalysts in air pollution control.